Index Card Match Learning Model with Cooperative Setting Think Pair Share Type Improves Early Mathematics Skills and Cooperation of Early Age Children - Arminiati, Ni Wayan; I Gusti Putu Suharta; Ketut Indra Purnomo (Universitas Pendidikan Ganesha, 2024)
Early mathematics and cooperative attitudes. Based on this, this study aims to analyze the effect of the index card match learning model with a cooperative setting of the think pair share type in improving early mathematics and cooperation skills in early childhood. This study is quasi-experimental with a non-equivalent post-test-only control group design. The population in this study were 184 children of Kindergarten B1. The sample selection technique used in this study was simple random sampling. The number of participants in this study was 46 children from kindergarten B. The method used in collecting data was a questionnaire. The instrument used in collecting data was a questionnaire sheet. The data analysis technique in this study was inferential statistics. The study results showed differences in the mathematics and cooperation skills of children who followed the Index Card Match learning model with a cooperative setting of the Think Pair Share type with children compared to those taught using the conventional model in Kindergarten B. It was concluded that the Index Card Match learning model with a cooperative setting of the Think Pair Share type can improve early mathematics and cooperation skills in early childhood. The research implies that using the Index Card Match learning model with a cooperative setting of the Think Pair Share type provides an exciting experience that teachers can use to create meaningful learning activities.